Comparison of inferior oblique muscle weakening by anterior transposition or myectomy: a prospective study of 20 cases. Issue 2 (1st February 1999) - Min, Byung-Moo; Park, Ju-Hee; Kim, Seung-Young; Lee, Seong-Bok
Abstract : BACKGROUND/AIMS: Among the various weakening techniques of inferior oblique muscle overaction, the most commonly used techniques include myectomy, recession, and anterior transposition. Anterior transposition and myectomy were compared to evaluate the surgical results in inferior oblique overaction. METHODS: 20 children with bilateral +3 overacting inferior oblique muscles underwent a prospective randomised study by which the anterior transposition procedure in one eye was compared with the myectomy procedure in the other eye. RESULTS: Postoperative follow up averaged 2 years. The success rates in two surgical procedures were 85% for the anterior transposition and 25% for the myectomy (standard of success was based on zero inferior oblique overaction). In only one case did the anterior transposition tend to limit the elevation of the eye in the midline, adduction, and abduction. Anterior transposition produced hypotropia at the primary position in only one case. Most eyes that underwent myectomy (75%) showed apparent residual overaction. CONCLUSION: The anterior transposition appeared to be more effective in eliminating the overaction of inferior oblique muscle than the myectomy.